CMPF Does Not Associate with Impaired Glucose Metabolism in Individuals with Features of Metabolic Syndrome - Lankinen, Maria A.; Hanhineva, Kati; Kolehmainen, Marjukka; Lehtonen, Marko; Auriola, Seppo; Mykkänen, Hannu; Poutanen, Kaisa; Schwab, Ursula; Uusitupa, Matti (PLOS ONE, 2015)
Objective 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid (CMPF) is a metabolite produced endogenously from dietary sources of furan fatty acids. The richest source of furan fatty acids in human diet is fish. CMPF was recently shown to be elevated in fasting plasma in individuals with gestational diabetes and type 2 diabetes, and mechanistically high level of CMPF was linked to β cell dysfunction. Here we aimed to study the association between plasma CMPF level and glucose metabolism in persons with impaired glucose metabolism. Methods Plasma CMPF concentration was measured from plasma samples of the study participants in an earlier controlled dietary intervention. All of them had impaired glucose metabolism and two other characteristics of the metabolic syndrome. Altogether 106 men and women were randomized into three groups for 12 weeks with different fish consumption (either three fatty fish meals per week, habitual fish consumption or maximum of one fish meal per week). Associations between concentration of CMPF and various glucose metabolism parameters at an oral glucose tolerance test at baseline and at the end of the study were studied. Results Fasting plasma CMPF concentration was significantly increased after a 12-week consumption of fatty fish three times per week, but the concentration remained much lower compared to concentrations reported in diabetic patients. Increases of plasma CMPF concentrations mostly due to increased fish consumption were not associated with impaired glucose metabolism in this study. Instead, elevated plasma CMPF concentration was associated with decreased 2-hour insulin concentration in OGTT. Conclusions Moderately elevated concentration of CMPF in plasma resulting from increased intake of fish is not harmful to glucose metabolism. Further studies are needed to fully explore the role of CMPF in the pathogenesis of impaired glucose metabolism. Trial Registration ClinicalTrials.gov NCT00573781